(untitled) - THIOLY, Francois
Collection of newspaper cuttings or extracts copied from Geneva newspapers, 1865-1866, 1873. The pages of the scrapbook have been numbered, but several pages are loose, or have been cut out: pp. 3/4 (loose); pp. 5/6 (missing); pp. 7/8 (loose) [cutting th
?Part of Montagnier bequest; (Montagnier died in 1933).
1865
1866
C
Keywords: Alps